Assessing the Effectiveness of Differentiated Instructional Approaches for Teaching Math to Preschoolers with Different Levels of Executive Functions - Aleksander N. Veraksa; Margarita S. Aslanova; Daria A. Bukhalenkova; Nikolay E. Veraksa; Liudmila Liutsko (MDPI AG, 2020)
Previous studies have found that the development of mathematical abilities, along with the development of executive functions, predict students' subsequent academic performance. The present study aimed to assess the effectiveness of teaching the concept of area to preschool children with different levels of cognitive processes (CP) including executive functions and short-term memory. The experiment introduced the concept by using three different instructional approaches: traditional, contextual, and modeling. The sample included 100 children aged 6-7 years (M = 6.5 years), of whom 43% were boys. Each experimental condition included children with low, middle, and high levels of CP, as determined based on the NEPSY-II subtests. The children with low CP levels showed higher results in assimilating the notion of area after being taught using the contextual approach. In contrast, children with high CP levels showed a higher mastery of the concept of area following the use of the modeling approach. The results suggest the importance of CP development in building ways of mastering mathematical content. This contributes to choosing the optimal path of teaching mathematics for preschoolers, taking into account the development of their cognitive processes to improve their academic performance.